Positioning the Pacific as a Disabling Environment: Reading of Kiana Davenport’s The House of Many Gods - Kristiawan Indriyanto (Indonesian Journal of English Language Studies (IJELS), 2020)
This study analyzes Kiana Davenport’s the House of Many Gods, a novel that contextualizes the issue of the nuclearized Pacific and the islanders’ exposure toward the toxic substance as an intersection between environmental/eco-criticism and disability studies. Deriving from Carrigan’s concept of disabling environment, this article foregrounds the continuation of western colonialism and nuclear militarism in the Pacific which is positioned as the periphery, far from the Western metropolitan center. The presence of nuclearized military installations in the Pacific articulates the unequal relationship between the metropolitan center and distant overseas colony in the Pacific as a site for experimentation. The novel dramatizes how the islanders are exposed toward dangerous and toxic substances which ravaged their bodies, denied their agency as healthy citizens, alienated them from their landscape (aina) and kept them in a state of continuous disablement. Employing Carrigan’s concept of disabling environment, this paper argues that the exploitation of indigenous people is legitimized under the guise of advancing Western scientific advancement. This study concludes that the Pacific islanders as it is represented in the House of Many Gods are instrumentalized as the ‘non-human’ in which their existence is necessary for the scientific progress of the Western powers.